Response of the Peanut (Arachis hypogaea L.) Cultivar Gregory to Interactions of Digging Date and Disease Management - Jordan, David L.; Johnson, P. Dewayne; Shew, Barbara B. (Advances in Agriculture, 2016)
Digging date can have a major impact on pod yield, market grade characteristics, and economic return of peanut (Arachis hypogaea L.) and can be influenced by environmental conditions and disease management. In 17 experiments from 2003 to 2012, economic return of peanut was determined over 5 digging dates spaced 1 week apart beginning in early to mid-September through mid-October. Linear, quadratic, and cubic relationships for economic return versus days after peanut emergence were observed in 3, 6, and 4 experiments, respectively, with no response to digging date observed in 4 experiments. In a second experiment from 2005 to 2012, relationships among canopy defoliation and economic return for peanut at 3 digging dates with 3 fungicide regimes were variable, although increasing the number of fungicide sprays decreased canopy defoliation and increased economic return for later digging dates. Applying a single late-season spray of fungicide as a rescue treatment reduced canopy defoliation in 4 of 8 years and affected economic value in 2 of 8 years.